Pemanfaatan Media Kartu Kata Untuk Meningkatkan Pemahaman Peserta Didik Terhadap Materi Kosakata Anggota Tubuh Kelas I SDN 1 Licin - Mayske Rinny Liando; Grace Engelin Kuron; Azizah Verdianti (JUPE : Jurnal Pendidikan Mandala, 2022)
The material or knowledge conveyed by utilizing the right learning media will produce something good, but if educators are not able to use the media properly, the material or knowledge they convey will not be maximally distributed. There are some materials that are difficult to convey or transfer to students, especially the intended students are low-grade students, namely the first grade of elementary school, one of which is about vocabulary material. The type of research used in this research is classroom action research(CAR). The purpose of classroom action research is to improve the implementation of the learning process in learning activities, especially in classroom learning and student learning outcomes. In the first cycle, the percentage value of student learning outcomes was 60% with a sufficient category. This increase occurred with the previous or pre-cycle results, namely the learning outcomes of students had a percentage of 50% in the less category. In the second cycle there has been an increase in learning outcomes using word cards for body parts vocabulary material with a percentage value of 95% with a very good category. Researchers assume that the media used to improve students' understanding will greatly determine the success of the learning carried out. Learning media is one of the determining factors for the success of the learning activities carried out.